2018
DOI: 10.1021/acs.organomet.7b00906
|View full text |Cite
|
Sign up to set email alerts
|

Osmium Catalysts for Acceptorless and Base-Free Dehydrogenation of Alcohols and Amines: Unusual Coordination Modes of a BPI Anion

Abstract: A novel type of catalyst precursors for the dehydrogenation of hydrogen carriers based on organic liquids has been discovered. Complexes OsH6(P i Pr3)2 (1) and OsH(OH)(CO)(P i Pr3)2 (2) react with 1,3-bis(6'-methyl-2'-pyridylimino)isoindoline (HBMePI) to give OsH3{κ 2-Npy,Nimine-(BMePI)}(P i Pr3)2 (3) and OsH{κ 2-Npy,Nimine-(BMePI)}(CO)(P i Pr3)2 (4). The unprecedented  2-Npy,Nimine coordination mode of BMePI is thermodynamically preferred with Os(IV) and Os(II) metal fragments and allows to prepare BMePI-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 125 publications
1
21
0
Order By: Relevance
“…The reactions were performed in toluene, at 100 °C, using a substrate concentration of 0.255 M and a catalyst concentration of 1.8 × 10 –2 ( 3 ) or 9.0 × 10 –3 ( 4 and 5 ) M: i.e., 7 mol % of the metal in all cases. Table collects the alcohols studied and the yield of carbonyl compound formed as a function of the catalyst, after 24 h. The previously reported conversions obtained with the mononuclear osmium catalyst OsH 3 {κ 2 -N py , N imine (BMePHI)}­(P i Pr 3 ) 2 are also included for comparison …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions were performed in toluene, at 100 °C, using a substrate concentration of 0.255 M and a catalyst concentration of 1.8 × 10 –2 ( 3 ) or 9.0 × 10 –3 ( 4 and 5 ) M: i.e., 7 mol % of the metal in all cases. Table collects the alcohols studied and the yield of carbonyl compound formed as a function of the catalyst, after 24 h. The previously reported conversions obtained with the mononuclear osmium catalyst OsH 3 {κ 2 -N py , N imine (BMePHI)}­(P i Pr 3 ) 2 are also included for comparison …”
Section: Resultsmentioning
confidence: 99%
“…Because it vacates three basic nitrogen atoms, the mononuclear species bearing the BMePHI ligand coordinated in this fashion can be employed to generate homoleptic and heteroleptic binuclear compounds, where the polydentate ligand acts as a μ-(κ 2 - N py , N imine ) 2 bridge. Frontier orbitals and electrochemical studies showed that the metal fragments behave independently in a sequential manner …”
Section: Introductionmentioning
confidence: 99%
“…Dihydride-dichloride 1 also activates the N-H bond of 1,3-bis(6'-methyl-2'pyridylimino)isoindoline (HBMePI), which is a sterically demanding version of 1,3bis(2-pyrilimino)isoindoline (HBPI). 69 The activation generates the isoindolinate anion BMePI and HCl. The latter is removed from the reaction medium with K t BuO.…”
Section: Sn-h Bond Activationmentioning
confidence: 99%
“…The reason for this novel preference is thermodynamic, since it gives rise to the most stable structure from all the possible options. 69 Accordingly, treatment of 2-propanol solutions of 1 with 0.5 equiv of HBMePI, in the presence of 0.5 equiv of K t BuO, at room temperature gives the salt The iridium center of 122 catalyzes the dehydrogenation of secondary alcohols to ketones, primary alcohols to aldehydes or esters, and diols to lactones.…”
Section: Sn-h Bond Activationmentioning
confidence: 99%
“…Thus, in contrast to 3, it oxidizes 1-diphenylmethanol better than 1phenylethanol (77% versus 60%). 18 Alcohols with two alkyl groups, such as 2-octanol and 1-cyclohexylethanol (runs 8 and 9) are dehydrogenated worse than diphenylmethanol. 2-Octanone and cyclohexyl methyl ketone are obtained in 40% and 50% yield, respectively.…”
Section: Dehydrogenation Of Secondary and Primary Alcohols And Diolsmentioning
confidence: 99%